THE INVESTIGATION EFFECT FACTORS ON CUSTOMER RELATIONSHIP MANAGEMENT IN BANKING INDUSTRY (CASE STUDY: CORPORATE BANKING) "MIX METHOD" - Asadi, Mehdi; Abdolvand, Mohammad; Hanzaee, Kambiz; Khounsiavash, Mohsen (Revista Inclusiones, 2019)
The purpose of this Paper is to Explore the Effect Factors on customer relationship management in the scope of the corporate banking by using a mixed method. mThis Research consist of two studies .In study 1, researchers carried out the recognition of dimensions and factors of customer relationship management and corporate banking by using phenomenological approaches, they also used the Grounded Theory approach in order to investigate relationships between these two main issues during the first study. In study 2, after determining the model, they carried out testing models. data Gathering In study 1, were provided by using the protocol based on interviewing with seven senior bank managers while applying a quantitative approach, and in study 2, questionnaire teams, deigned & distributed among 330 corporate banking customers of a three private banks, after investigating the content and construct validity, The Maxqda 12 pro software was applied in the first study in order to analyze interviews, and AMOS software was utilized in the second study. In the quantitative phase,The researcher identifies 278 open codes, then classifies them into 6 Axial Codes and finally, identifies relationships between the two main issues of customer relationship management and corporate banking by using the selective coding.